Bibliometric analysis of psychometrics in sports and physical education - Triansyah, Andika; Subarjah, Herman; Hidayat, Yusuf; Lukitowati, Suci; Agus, Herdiansyah (Lambung Mangkurat University, 2025)
The study of psychometrics in sports and physical education has developed over time and has become an international concern. So this study aims to find trends in themes that are popularly used in psychometric studies in sports and physical education based on Scopus-indexed articles. The research method used to conduct the analysis is bibliometrics. Search and filtering strategies use PRISMA flowcharts. The research review used data in Comma-Separated Values (CSV) format, which was then exported to Microsoft Excel to visualize the search results of bibliometric analysis, the tool used was VOSviewer. The results of the analysis of the development of psychometric publications in sports and physical education explain the trend of publications, journals, and authors with the highest citations, the publication network between countries, and the most widely used keywords. The conclusion of the study results in the development of psychometric publications in sports and physical education in the period 1981-2023 tends to increase. This shows that the trend of research with psychometric topics in sports and physical education is of international concern.